Aurintricarboxylic acid prevents GLUR2 mRNA down-regulation and delayed neurodegeneration in hippocampal CA1 neurons of gerbil after global ischemia - Aronica, Eleonora M. (The National Academy of Sciences, 1998)
Aurintricarboxylic acid (ATA), an inhibitor of endonuclease activity and other protein–nucleic acid interactions, blocks apoptosis in several cell types and prevents delayed death of hippocampal pyramidal CA1 neurons induced by transient global ischemia. Global ischemia in rats and gerbils induces down-regulation of GluR2 mRNA and increased α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-induced Ca(2+) influx in CA1 before neurodegeneration. This result and neuroprotection by antagonists of AMPA receptors suggests that formation of AMPA receptors lacking GluR2, and therefore Ca(2+) permeable, leads to excessive Ca(2+) influx in response to endogenous glutamate; the resulting delayed neuronal death in CA1 exhibits many characteristics of apoptosis. In this study, we examined the effects of ATA on expression of mRNAs encoding glutamate receptor subunits in gerbil hippocampus after global ischemia. Administration of ATA by injection into the right cerebral ventricle 1 h before (but not 6 h after) bilateral carotid occlusion prevented the ischemia-induced decrease in GluR2 mRNA expression and the delayed neurodegeneration. These findings suggest that ATA is neuroprotective in ischemia by blocking the transcriptional changes leading to down-regulation of GluR2, rather than by simply blocking endonucleases, which presumably act later after Ca(2+) influx initiates apoptosis. Maintaining formation of Ca(2+) impermeable, GluR2 containing AMPA receptors could prevent delayed death of CA1 neurons after transient global ischemia, and block of GluR2 down-regulation may provide a further strategy for neuroprotection.